Everything Is Science: A Free City-Wide Science Festival - Creameans, Jarrod W.; Pitts, Michelle G.; White, Olivia; Greenwell, Kellen M.; Colón, Kristie; Garneau-Tsodikova, Sylvie; Venditto, Vincent J. (Frontiers in Communication, 2020)
A week-long, city-wide science festival called Everything is Science (EiS) was developed to educate the community in an informal manner. The festival serves as a platform for presenters from diverse professions to give engaging talks (without PowerPoint slides) to the public, free of charge, in restaurants and bars around town. Over 350 people attended the events over five days with 33 presenters. Surveys completed by attendees and session coordinators indicate strong support for this festival. Altogether, the EiS festival serves as a no-cost method to engage with the community and improve science literacy with potential for adoption in other cities.